Question 1)
Given: F(x) = 3x^2 + 1, G(x) = 2x - 3, H(x) = x
F(G(x)) = 3(2x - 3)^2 + 1
F(G(x)) =3(4x^2 - 12x + 9) + 1
F(G(x)) = 12x^2 - 36x + 27 + 1
F(G(x)) =12x^2 - 36x + 28
Question 2)
Given: F(x) = 3x^2 + 1, G(x) = 2x - 3, H(x) = x
H -1 (x) = x (inverse)
Percent formula : is/of = %/100
is = 48
of = 160
% = x
48/160 = x/100
cross multiply
160x = 4800
x = 4800/160
x = 30......so 48 is 30% of 160
Answer:
............................
Answer:
578.50
Step-by-step explanation:
The worker worked 40 hours at 13 dollars
40 * 13 =520
Then they worked 3 hours at 13(1.5) or 19.50
3*19.50 =58.5
The total amount of money earned is regular time plus overtime
520 + 58.5 =578.50
Answer:
Step-by-step explanation:
-a + 6b = -3 + 6 * (-6) = -3 - 36 = -39